Statistical Inference for Harmonic New Better Than Renewal Used in Expectation Class of Life Distributions Under Random Progressive Censoring - Elkahlout, Gamal R. (Journal of Reliability and Statistical Studies, 2026)
This paper extends the theoretical framework and testing methodology for the Harmonic New Better (or Worse) than Renewal Used in Expectation classes of life distributions. We revisit and refine empirical test statistics under random censoring, incorporating progressive Type II censoring schemes to enhance applicability. Modern lifetime distributions, including Lognormal, Gumbel, and Weibull models, are incorporated into the power analysis, with results strengthened through Monte Carlo simulations, bootstrap confidence intervals, and variance estimates. The findings highlight the robustness and practical value of the proposed methods, particularly in small-sample scenarios, and provide guidance for implementation through readily available software tools.